The Use of Interactive Digital Media as a Strategy to Strengthen Arabic Vocabulary in Students at SD IT Kautsar Ilmi Sijunjung - Khairanis, Retisfa; Aldi, Muhammad (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This community service activity aims to improve the Arabic vocabulary of students at SD IT Kautsar Ilmi Sijunjung through the use of interactive digital media. The background of this activity stems from low vocabulary retention, a lack of variety in learning media, and the dominance of conventional methods, which cause students to be less enthusiastic about attending lessons. This community service program uses a Participatory Action Approach that involves teachers and students in three stages, namely preparation, implementation, and evaluation. Digital media such as Wordwall, Quizizz, and LearningApps were used as game-based learning tools to strengthen vocabulary comprehension. Success was measured through observation, interviews, and comparison of pre test and post test scores. The results of the activity showed a significant increase in students' ability to recognize and remember vocabulary and apply it in simple sentences, as seen from the increase in post-test scores on all assessment indicators. In addition, there were positive changes in learning attitudes, such as increased motivation, confidence, and student activity in participating in learning. Teachers also gained increased competence in utilizing educational technology. Although there were obstacles such as limited devices and networks, solutions through small group divisions made the activities continue to run effectively. Overall, the use of interactive digital media has proven to have a positive and sustainable impact on improving the quality of Arabic language learning. [Kegiatan pengabdian masyarakat ini bertujuan meningkatkan penguasaan mufradat Bahasa Arab siswa SD IT Kautsar Ilmi Sijunjung melalui penggunaan media digital interaktif. Latar belakang kegiatan ini berangkat dari rendahnya retensi kosakata, kurangnya variasi media pembelajaran, serta dominannya metode konvensional yang menyebabkan siswa kurang antusias dalam mengikuti pelajaran. Pengabdian ini menggunakan pendekatan Participatory Action Approach yang melibatkan guru dan siswa dalam tiga tahap, yaitu persiapan, implementasi, dan evaluasi. Media digital seperti Wordwall, Quizizz, dan LearningApps diterapkan sebagai sarana pembelajaran berbasis permainan untuk memperkuat pemahaman mufradat. Pengukuran keberhasilan dilakukan melalui observasi, wawancara, serta perbandingan nilai pre test dan post test. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada kemampuan siswa dalam mengenali dan mengingat mufradat serta menerapkannya dalam kalimat sederhana, yang terlihat dari meningkatnya skor post-test pada seluruh indikator penilaian. Selain itu, terjadi perubahan positif pada sikap belajar, seperti meningkatnya motivasi, kepercayaan diri, dan keaktifan siswa dalam mengikuti pembelajaran. Guru juga memperoleh peningkatan kompetensi dalam memanfaatkan teknologi pendidikan. Meskipun terdapat kendala seperti keterbatasan perangkat dan jaringan, solusi melalui pembagian kelompok kecil membuat kegiatan tetap berjalan efektif. Secara keseluruhan, penggunaan media digital interaktif terbukti memberikan dampak positif dan berkelanjutan dalam peningkatan kualitas pembelajaran Bahasa Arab.]